Drug-induced osteonecrosis of the jaws: Narrative literature review (Research, Society and Development, 2024)
Osteonecrosis is a pathological bone disorder in which bone tissue necrosis occurs without prior infection. Bisphosphonate-associated osteonecrosis of the jaws (BFS) was first described in 2003 by Marx. However, the current nomenclature was modified by the American Association of Oral and Maxillofacial Surgeons (AAOMS) to drug-related osteonecrosis of the jaws (MRONJ), maintaining the description as an effect of several other classes of drugs. This study aimed to carry out a narrative literature review on the pathogenesis of Drug-Induced Osteonecrosis of the Jaws (DIOJ), changes in the jaws, diagnosis and what treatments can be carried out, as well as preventive measures. In addition, the aim was to analyze and identify which drugs induce osteonecrosis in the oral cavity and the procedures at risk of this alteration. The methodology used was a search of various authors and references on a specific topic with a qualitative approach. A survey was carried out of articles researched in the Google Scholar and VHL databases with research correlated to the topic of osteonecrosis of the jaws caused by medication. Articles from 2003 to 2023 were included. More studies on OMIM need to be carried out, but regular monitoring and maintenance of oral health by a dental surgeon and the inclusion of this professional in a multi-professional team is essential to reduce the complications that affect the oral cavity.